6.Detection of Escherichia coli Contamination in Vaname Shrimp (Litopenaues vannamei) at Fish Auction Place (TPI) Lampulo Banda Aceh - Wilyo Hendro Fauzan; Wahyu Eka Sari; Andi Novita; Faisal Jamin; Razali Daud5; Rastina Rastina; Safika Safika (Jurnal Medika Veterinaria, 2021)
Shrimp is an easily polluted material, so it requires good handling. Contamination can occur during harvest, handling, or transportation. This study aims to detect Escherichia coli contamination in vaname shrimp sold at TPI Lampulo Banda Aceh. A total of 10 samples of vaname shrimp were obtained from 10 merchants at TPI Lampulo. The research method used is observational, and the data analysis is done descriptively. The detection of E. coli contamination was carried out by the total plate count (TPC) test method. Based on the study results, two of the 10 samples of vaname shrimp merchant detected E. coli bacterial contamination, namely the results of sample 01 merchant indicated the number of TPC 2x102 CFU/g and in 09 merchants indicated the number of TPC 11x101 CFU/g. The TPC results were indicated by the growth of E. coli colonies on eosin methylene blue agar (EMBA) media after incubation for 24 hours at 37 ºC. The number of the two detected positive samples showed less than 1x103 CFU/g by the provisions of SNI 2332.3:2015. Thus, it can be concluded that E. coli contamination was detected in vaname shrimp sold by the merchant at TPI Lampulo but did not exceed the SNI threshold, so it was safe for consumption.